Kras Diagnosing the Little-Known Cancers Oncogene through Liquid Biopsy: Review - Hafiz Syed Mohammad Osama Jafri; Saeeda Baig; Shamim Mushtaq; Jawed Malik; Sabra Siraj (ziauddin University, 2020)
Tissue biopsy, till date, is a gold standard for tumor diagnosis, grading, treatment, and detecting genetic evidences for identifying appropriate personalized treatments. However, it is painful, invasive, expensive, and risky making sequential biopsies basically impractical. Detection of Kras genes through liquid biopsy is the growing theragnostic technique, which is more sensitive, specific, much cost-effective and quick method for detecting the mutational status of cancers. Liquid biopsy detects biomarkers present in various body fluids, such as plasma, urine, saliva and cerebrospinal fluid, harboring cancer degraded fragments and cells shed by carcinoma such as circulating tumor cells, microRNA and circulating tumor DNA. It can be utilized as a pre-screening test for initial stage cancers also where multiple sampling is required for monitoring cancer therapies. Kras is the most extensively mutated cancer oncogene involve in altering the downstream signaling pathways, increasing oncogenic signaling, which is typically associated with poor prognosis and resistance to therapy. This review was conducted to clarify its prognostic significance as well as its mutational role in different carcinomas. To identify studies related to Kras mutation Medline, PubMed, Google Scholar and Web of Science search engines were explored and forty two relevant researches were finalized from year 2005 to 2019.